Analysis of the effectiveness of calcium hydroxide removal with variation of technique and solvent vehicles - Paula Dias Lins; Barbara Catarina Lima Nogueira; Nathália Carolina Fernandes Fagundes; Fernando Romualdo Bezerra Silva; Rafael Rodrigues Lima (Wolters Kluwer Medknow Publications, 2015)
Context: Calcium hydroxide (Ca(OH)2) paste filling is largely used as intra-canal medication and can be combined with different vehicles. Removal of that paste should be preceded by obturation, to avoid the occurrence of apical microleakage. Aims: To evaluate the efficiency of removal of pulp Ca(OH)2, from using different vehicles (water, propylene glycol) and removal techniques (mechanical and ultrasonic). Study Design: Twenty-four premolars and four human incisors were prepared with step-back technique and divided into six groups according to the removal techniques and vehicles used: Group distilled water/mechanical removal, Group distilled water/ultrasonic removal, Group propylene/mechanical removal, Group propylene/ultrasonic removal, negative control group, and positive control group. The differences between groups were analyzed. Materials and Methods: The teeth were prepared by step-back technique. The samples were evaluated by stereomicroscopy, using a scoring system for the evaluation of residues in the canal. Statistical Analysis: Mann-Whitney test was used to a comparison between groups with the same vehicle. For comparison between groups, regardless of the vehicle, we used the Kruskal-Wallis test, considering P < 0.05 for both tests. Results: Groups using distilled water or propylene glycol did not show statistically significant results. When the groups were compared, differences were detected between groups distilled water/propylene and mechanical removal/removal ultrasonic, with thefirst featuring superior performance. Conclusion: None of the removal techniques employed in this study was able to completely remove Ca(OH)2 from the root canal. However, the use of distilled water as a vehicle and ultrasonic removal presented the best performance.